-2(y-6)+1=0

Simple and best practice solution for -2(y-6)+1=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(y-6)+1=0 equation:


Simplifying
-2(y + -6) + 1 = 0

Reorder the terms:
-2(-6 + y) + 1 = 0
(-6 * -2 + y * -2) + 1 = 0
(12 + -2y) + 1 = 0

Reorder the terms:
12 + 1 + -2y = 0

Combine like terms: 12 + 1 = 13
13 + -2y = 0

Solving
13 + -2y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-13' to each side of the equation.
13 + -13 + -2y = 0 + -13

Combine like terms: 13 + -13 = 0
0 + -2y = 0 + -13
-2y = 0 + -13

Combine like terms: 0 + -13 = -13
-2y = -13

Divide each side by '-2'.
y = 6.5

Simplifying
y = 6.5

See similar equations:

| X(y+5)=66 | | -65=-8x-9 | | 2a^2+8ab=0 | | 2/9*9-4 | | lnx(x^4/4) | | 7a-4a-2a=5 | | 1441/2 | | 5x(x-3)= | | n(3n+2)=0 | | (5x+y)= | | 10p+9-11-p=-4p-8-6p | | 95=25+10*x | | ln(6x+6)=ln(5x+2) | | 3sinx/8 | | 2x+23=3x | | -8+30+-9= | | 11+n=27 | | 6*x-2*x=520 | | x-2*6*x=520 | | sin(x)+5x=0 | | x=5log(x) | | x-2*y=520 | | x*x-9x=-18 | | x-5log(x)=0 | | 9=-3(2b+7) | | 2x^2w^5*8x*2w^4= | | 6x+30=2x+10 | | 2x^2+3x-4=8x-4 | | 3ab*2cd=4ac | | 5(3a-2)=50 | | 2x*2x=4x | | (M+3)x^2+2m(x+1)+3=0 |

Equations solver categories